LANGKAH PRAKTIS MENYUSUN LAPORAN KINERJA DOSEN - Erawanto, Udin; Triantoro, Miranu (JANITA : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The lecturer performance report is a general description of a lecturer’s obligations in carriying out the tri dharma of higher education in each current semester, which includes education and teaching, research activities, community service and also supporting elements. Based on existing provisions, all lecturers must report their performance. However, the facts show that there are still some lecturers who have not prepared reports every semester. It is hoped that this community service activity will be able to stimulate and bridge lecturers to truly have the will and ability to prepare LKD to control their development as lecturers.